A prospective study in children with a severe form of atopic dermatitis: clinical outcome in relation to cytokine gene polymorphisms - Kayserova, J; Sismova, K; Zentsova-Jaresova, I; Katina, S; Vernerova, E; Polouckova, A; Capkova, S; Malinova, V; Striz, I; Sediva, A (Journal of investigational allergology & clinical immunology, 2012)
BACKGROUND AND OBJECTIVE: The course of atopic dermatitis (AD) in childhood is characterized by typical changes in phenotype, including a shift from skin involvement to respiratory allergy usually around the third year of age. We thus designed a prospective study to monitor the outcome of severe AD and to investigate the association between cytokine gene polymorphisms and clinical manifestations. METHODS: Clinical and laboratory follow-up of 94 patients with severe AD and 103 healthy controls was performed using routine methodology. Allele, genotype, and haplotype frequencies of single nucleotide polymorphisms of 13 selected cytokine/receptor genes were analyzed using PCR with sequence-specific primers. RESULTS: In our study, genotypes of 7 polymorphisms--LL-4 -1098G/T and -590C/T, IL-6 -174C/G and nt565A/G, and IL-10 -1082A/G, -819C/T, and -592A/C were significantly associated with atopic AD (P < .05). A significant association was also found for TNF-alpha AA and IL-4 GC haplotypes and AD. We confirm the progressive clinical improvement of AD together with a decrease in the severity index SCORAD (SCORing atopic dermatitis) during childhood (P < .05). We found significant differences between IL-4Ralpha +1902 A/G and positivity of tree pollen-specific IgE (P < .05) in the AD group. Moreover, a weak association was also found between IL-10 -819C/T and IL-10 -590A/C and the appearance of allergic rhinitis (P < 0.1). CONCLUSIONS: We confirmed a clinical shift in allergic phenotype in the first 3 years of life, and showed an association between IL-4, IL-6, and IL-10 polymorphisms and AD. Our data indicate that IL-4alpha and IL-10 polymorphisms may be considered predictive factors of respiratory allergy in children with AD.
Keywords: sezónní alergická rýma; Female; Genotype; Infant; předškolní dítě; novorozenec; Dermatitis, Atopic; Tumor Necrosis Factor-alpha; ženské pohlaví; jednonukleotidový polymorfismus; Gene Frequency; lidé; interleukiny; Infant, Newborn; Polymorphism, Single Nucleotide; genotyp; genetická predispozice k nemoci; studie případů a kontrol; atopická dermatitida; následné studie; Genetic Predisposition to Disease; frekvence genu; Rhinitis, Allergic, Seasonal; TNF-alfa; prospektivní studie; Follow-Up Studies; Male; progrese nemoci; Case-Control Studies; kojenec; Haplotypes; Prospective Studies; Disease Progression; Child, Preschool; alely; Alleles; Interleukins; haplotypy; mužské pohlaví; Humans